Life Span Extension by Reduction in Growth Hormone-Insulin-Like Growth Factor-1 Axis in a Transgenic Rat Model - Shimokawa, Isao (American Society for Investigative Pathology, 2002)
The longer life span in dwarf mice suggests that a reduction in the growth hormone (GH)-insulin-like growth factor (IGF)-1 axis retards aging and extends the life span in mammals. We tested this hypothesis in a transgenic strain of rats whose GH gene was suppressed by an anti-sense GH transgene. Male rats homozygous for the transgene (tg/tg) had a reduced number of pituitary GH cells, a lower plasma concentration of IGF-1, and a dwarf phenotype. Heterozygous rats (tg/−) had an intermediate phenotype in plasma IGF-1, food intake, and body weight between tg/tg and control (−/−) rats. The life span of tg/tg rats was 5 to 10% shorter than −/− rats. In contrast, the life span of tg/− rats was 7 to 10% longer than −/− rats. Pathological analysis suggested that neoplasms caused earlier death in tg/tg rats; in contrast, tg/− rats had reduced nonneoplastic diseases and a prolonged life span. Immunological analysis revealed a smaller population and lower activity of splenic natural killer cells in tg/tg rats. The results of the present study support the hypothesis, but suggest that there is an optimal level of the GH-IGF-1 axis to maximize survival in mammals.